A post-marketing study on interferon β 1b and 1a treatment in relapsing-remitting multiple sclerosis: different response in drop-outs and treated patients. Issue 12 (24th November 2003) - Milanese, C; La Mantia, L; Palumbo, R; Martinelli, V; Murialdo, A; Zaffaroni, M; Caputo, D; Capra, R; Bergamaschi, R
Abstract : Background: Interferon β 1b (Betaferon) and 1a (Avonex) were licensed in Italy for treating relapsing-remitting multiple sclerosis in February 1996 and August 1997, respectively. Objectives: To evaluate the effectiveness of these agents on the basis of clinical experience in northern Italian multiple sclerosis centres. Design: Clinical data on patients with relapsing-remitting multiple sclerosis were collected on an appropriate form from 65 centres in northern Italy. Intention to treat analysis was not possible, so patients who discontinued treatment (drop-outs) and who continued treatment (treated) were analysed separately. The main outcome measures were annual relapse frequency, number of relapse-free patients, mean change in extended disability status scale score (EDSS), and number of patients who worsened. Results: 1481 patients were included; 834 were treated with Betaferon and 647 with Avonex for mean periods of 21.4 and 12.0 months, respectively. Basal EDSS was 2.37 and 2.17, respectively, and relapse frequency was 1.62 and 1.45. The annual relapse rate decreased by more than 60% with Betaferon and 55% with Avonex. The proportions of relapse-free, improved, and worsened patients were similar in the two groups. More patients interrupted treatment with Betaferon (41.1%) than with Avonex (15.3%); such patients showed more active disease at baseline and during treatment. The incidence of side effects was higher in Betaferon treated patients. Conclusions: The effectiveness of Betaferon and Avonex is confirmed. There was a more marked effect than expected from the experimental trial results. This might reflect differences in inclusion criteria, or, more likely, loss of drop-outs, favouring selective retention of responders.